Η Τεχνη Γραμματικη - Ars Grammatica - Quirós R., Manuel Antonio (Universidad de Costa Rica, 2005)
This paper deals with grammar: its definition, goal, etymology, division, a little history and comparison to linguistics. Since Antiquity, normative grammar has filled a huge importance for culture and education of almost all people. Some latinisms in the field of grammar conclude the work.